The corruption of co-design political and social conflicts in participatory design thinking - Busch, Otto von 1975-; Palmås, Karl (New York Routledge, 2023)
Designers are often depicted as social change agents that serve the good in the world. Similarly, codesign tends to be described as a democratic mode of creativity that is somehow beyond reproach. But is change a virtue in itself, and do participatory practices always produce socially beneficial outcomes?

Such questions are becoming more pressing as codesign has emerged as a dominant practice in planning and urban design, while also informing corporate management and public administration. In this book, Otto von Busch and Karl Palmås suggest that designers tend to over-emphasise the place of ideals in design, leaving them ill-equipped to deal with a social world of power-wielding and zero-sum games. Seeking to re-orient the concerns of the Scandinavian tradition of participatory design, they suggest that co-design processes are rife with betrayals, decay and corruption, and that designerly empathy has morphed into a new form of cunning statecraft.

In putting forward Realdesign as an alternative conception of design practice, von Busch and Palmås ask: What hard lessons about the social must today's designers learn from realists like Machiavelli?"--
1 Introduction : the problems of participatory design -- 2 The realist challenge : power and possibilities -- 3 Betrayal : post-political participation -- 4 Corruption : design and decay -- 5 Cunning : mêtis and designerly statecraft -- 6 Hypocrisy : of virtue and vice -- 7 Closing propositions : after empathy, realdesign.
Includes bibliographical references and index.
Keywords: Architecture and society; City planning -- Social aspects; Design -- Social aspects